Acute effects of resistance training on cytokines and osteoprotegerin in women with metabolic syndrome. (17th October 2012) - Pereira, Guilherme B.; Tibana, Ramires A.; Navalta, James; Sousa, Nuno M. F.; Córdova, Claudio; Souza, Vinícius C.; Nóbrega, Otávio T.; Prestes, Jonato; Perez, Sergio E. A.
Summary Chronic inflammation has been identified as an important component of metabolic syndrome (MetS). Inhibition of the inflammatory mediator signals is a promising strategy against insulin resistance, atherosclerosis and other problems associated with MetS. Regular exercise decreases the components associated with MetS, including inflammatory cytokines. However, the relationship between an acute resistance training (RT) session, cytokine levels and MetS is unclear. Therefore, the aim was to evaluate the effects of a single bout of acute RT on tumour necrosis factor (TNF‐α), interleukins (IL) IL‐1a, IL‐1β, IL‐12, IL‐6, IL‐10 and osteoprotegerin (OPG) in women with MetS. Twenty‐four women were divided into 2 groups: metabolic syndrome (MetS) and non‐metabolic syndrome (Non‐MetS). After the familiarization and testing for 1 repetition maximum (1RM), participants completed 3 sets of 10 repetitions in the following exercises: machine leg press, leg extension, leg curl, chest press, lat front pull‐down and machine shoulder press with 60% of 1RM followed by 15 repetitions of abdominal crunches. A rest interval of 1 min was allowed between sets and exercises. Plasma TNF‐α, IL‐1a, IL‐1β, IL‐12, IL‐6, IL‐10 and OPG were measured before, immediately post and 60 min after RT. MetS group showed significantly higher concentrations of IL‐1β (P = 0·024) and IL‐6 (P = 0·049) and a trend for higher TNF‐α values (P = 0·092) compared with Non‐MetS. There was no group × time interactions after the RT session on the measured cytokines and osteoprotegerin. In conclusion, acute RT session induced no additional increase in pro‐inflammatory cytokines nor a decrease in anti‐inflammatory cytokines and OPG in women with MetS.